Meningkatkan Kesadaran Gizi Seimbang untuk Tumbuh Kembang Anak Optimal Membangun Generasi Unggul - Rohmah, Syifa; Pujiono, Imam Prayogo; Firdausi, Muhammad Izzat; Darutama, Ardiyan; Kurniawan, Indra; Fitroh, Qorry Aina (Pakis Journal Institute, 2025)
Stunting is one of the serious nutritional problems in Indonesia, with long-term impacts that are very detrimental to children's physical and cognitive development. One of the main factors causing high stunting rates is the lack of public knowledge regarding the importance of healthy eating patterns and providing proper nutrition for mothers. pregnant and toddlers. Community service programs that focus on preventing stunting can make a significant contribution in increasing public awareness regarding the importance of providing balanced nutrition for children under five and toddlers. This community service method will implement the ABCD (Asset-Based Community Development) approach to achieve the goal of stunting prevention. It is hoped that after this service activity can increase public knowledge and awareness about the importance of balanced nutrition, as well as improve eating behavior among mothers of toddlers and toddlers.